Sustainable Energy Management at KMUTT Thailand - Prasert Kanthamanon (Universitas Diponegoro, 2022)
King Mongkut’s University of Technology Thonburi (KMUTT) committed to be Sustainable University for SDGs 2030 since 2017 and committed to sustainability leadership in all of our activities from operations, teaching, to conducting research. Our commitments are to be a sustainable university providing a role model on Energy, Environment, Safety Management Systems and provide sustainability platform to promote sustainability leadership. Sustainable energy management system has been provided by top management policy since 2010 which focus on energy usage reduction, energy efficient appliances usage, renewable energy usage and carbon footprint reduction. To achieve the sustainable energy goal which comply to SDG 7: Affordable and Clean Energy and SDG13: Climate Action, KMUTT focus on student leadership which provide awareness raising, perception, and leading to implementation for all in KMUTT by using SEP for SDG concept. Moreover, KMUTT initiate sustainable strategy which provide the learning environment to make all campus as living lab, promote people participation and monitoring to make continual improvement with positive reinforcement. The sustainable energy goal achieved along with the expansion activities to community surround according to the student engagement. Keyword: energy management, sustainable energy, SEP for SDG, SDG 7, SDG 13